Author Correction: Ophiopogonin D maintains Ca2+ homeostasis in rat cardiomyocytes in vitro by upregulating CYP2J3/ EETs and suppressing ER stress - You Wen-ting; Zhou Tao; Ma Zeng-chun; Liang Qian-de; Xiao Cheng-rong; Tang Xiang-lin; Tan Hong-ling; Zhang Bo-li; Wang Yu-guang; Gao Yue (Acta Pharmacologica Sinica; Vol 41, No 12 (December 2020): Acta Pharmacologica Sinica, 2020)
The authors realized that the representative images of DMSO group in Fig. 7a were found to be misplaced due to the mishandling in the paper preparation. All the authors agree on the correction of our negligence and the correct images are given below. This correction does not affect the results and conclusion of the original paper. We sincerely apologize for the mistake and any inconvenience this might have caused.